ANTESEDEN MINAT BELI PADA E-COMMERCE LAZADA DENGAN KEPERCAYAAN KONSUMEN SEBAGAI VARIABEL INTERVENING: (Survei pada Masyarakat Kabupaten Kuningan) - Amalia Cantika; Wachjuni; Vigory Gloriman Manalu (Digital Business and Entrepreneurship Journal, 2023)
The purpose of this study was to analyze whether electronic word of mouth and celebrity endorsers affect purchase intention in e-commerce Lazada through consumer trust. The research method used is descriptive research method with the population in this study is the Kuningan Regency community who have visited and have never made a purchase at Lazada e-commerce whose number is unknown. The sampling technique used a non-probability technique with a sample of 200 respondents. The data collection technique used in this study was by distributing questionnaires and measuring them using an interval scale. The analytical tool used in this research is SEM AMOS. The results showed that: (1) E-WOM positively and significantly affected purchase intention in Lazada's e-commerce. (2) Celebrity endorsers have a significant effect on purchase intention in Lazada e-commerce. (3) E-WOM positively and significantly affects consumer confidence in Lazada e-commerce. (4) Celebrity endorsers have a positive and significant effect on consumer confidence in Lazada e-commerce. (5) Consumer trust positively and significantly affects purchase intention in Lazada e-commerce. Keywords: electronic word of mouth; celebrity endorser; purchase intention; consumer trust